Birth data clustering to segmentation delays in birth certificate registration - Hasmin, Erfan; Rahman, Aedah Abd (International Journal of Advances in Applied Sciences, 2025)
Timely and accurate birth registration is essential for ensuring access to vital public services. This study focuses on clustering birth data to identify patterns in registration delays, using data mining techniques such as the K-means algorithm. By clustering birth data from Makassar City, Indonesia, based on various demographic and birth-related criteria, the study segments the data into groups that reflect both timely and delayed registrations. The optimal number of clusters is determined using the elbow and silhouette methods. Results show that a three-cluster configuration effectively captures patterns in birth registration delays, offering critical insights for policymakers. These findings provide a foundation for improving birth registration processes, ensuring more timely registration, and guiding data-driven public policy decisions.